PERILAKU KONSUMEN HIJAU INDONESIA : TINJAUAN SUDUT DEMOGRAFI DAN PSIKOGRAFI - Evi Vileta Lanasier (Media Riset Bisnis & Manajemen, 2002)
Research about green marketing ałways focus by how the behavior of the green consumer for the marketing practice that done by the company. The goal of the research is want to test the green consumer from the demography point to view like age, sex, education rate and income rate and psychography point of view (percieved consumers, effectiveness, environmental concem, and political orientation) beside to look the profile of the green consumer in Indonesia.